2017
DOI: 10.1108/lodj-07-2015-0142
|View full text |Cite
|
Sign up to set email alerts
|

How can financial organizations improve employee loyalty? The effects of ethical leadership, psychological contract fulfillment and organizational identification

Abstract: Purpose The purpose of this paper is to examine the impact of ethical leadership on the financial professionals’ loyalty by focusing on the mediating effects of perceived psychological contract fulfillment (PPCF) and organizational identification (OI). Design/methodology/approach A questionnaire survey was used in this research. Findings Financial professionals in Taiwan were recruited for the sample. The results revealed that the professionals’ experiences of ethical leadership positively associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 99 publications
0
27
0
1
Order By: Relevance
“…Therefore, PLS is sufficient to establish and develop the theory [65] or to check the theory which is in its initial phase [67], hence very suitable in this research. In addition, SEM is especially suggested to analyse the mediation [68], and ample of research work employed this statistical approach in estimating such relationship using PLS [69][70][71]. Likewise, the PLS through WarpPLS 5.0 was employed to test the hypotheses and goodness of the model fit.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PLS is sufficient to establish and develop the theory [65] or to check the theory which is in its initial phase [67], hence very suitable in this research. In addition, SEM is especially suggested to analyse the mediation [68], and ample of research work employed this statistical approach in estimating such relationship using PLS [69][70][71]. Likewise, the PLS through WarpPLS 5.0 was employed to test the hypotheses and goodness of the model fit.…”
Section: Discussionmentioning
confidence: 99%
“…In general, some empirical studies showed that PCF and employee attitudes are intertwined around organization elements including work performance, organizational citizenship behavior, corporate trust, employee turnover, etc. (Johnson and O'Leary-Kelly, 2003;Sturges et al, 2005;Katou and Budhwar, 2012;Tseng and Wu, 2017). Members of the organization receiving appropriate PCF have higher trust, retention intentions and perceived organizational support (Coyle-Shapiro and Kessler, 2000;Turnley et al, 2003).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…It is hope through these two factors too can it enforces employees' loyalty towards the organization. By definition, employee loyalty is the ability of an employee to stay and be faithful to the organization for a certain extent 13,14 . However, a more comprehensive definition of job loyalty, employee's commitment towards the organization also included.…”
mentioning
confidence: 99%